Nonlinear Cascaded Control for a DC-DC Boost Converter - Mansouri, Amirhosein; Gavagsaz-Ghoachani, Roghayeh; Phattanasak, Matheepot; Pierfederici, Serge (Universitas Muhammadiyah Yogyakarta, 2023)
The Boost Converter is a type of DC-DC converter that operates using switching techniques and is designed to elevate the voltage level. This paper presents a cascaded control for a boost converter to ensure that the inductor current and output capacitor voltage remain in a safe operating zone. Ensuring safe operating conditions and stable closed-loop poles is crucial because it guarantees that both current and voltage remain within the designated operating range. This preventive measure prevents any damage to components like capacitors (C), inductors (L), and switches. Unstable operation, on the other hand, could lead to oscillations and an undesirable increase in the amplitude of current and voltage, posing a risk to all components involved. The research contribution involves an investigation of cascaded control, utilizing power and energy concepts due to their advantageous effects on system performance and design. By implementing nonlinear controllers based on a large-signal averaged model, the closed-loop poles remain independent of operating points, eliminating the need for small-signal linearization. Small-signal linearization makes the controlled system dependent on the operating point. Two controllers are introduced based on power and energy concept, which is easy to understand. The potential practical application of the proposed cascaded control approach is in high-power applications. Tracking the energy stored in the output capacitor is first investigated to validate the proposed control scheme by varying the output voltage reference from 32 V to 50 V. Then, the regulation of the energy voltage is explored by varying the load resistance for the output voltage at 50 V. Both are done using a switched model using MATLAB/Simulink software. Simulation results are given to demonstrate the effectiveness of the proposed method. The key metrics used to assess the effectiveness of the proposed control scheme are the undershoot voltage and robustness. The results show that the studied system's tracking, regulating operations and robustness properties are as expected. The proposed method faces a challenge with the number of sensors required. To address this, observers can be utilized to reduce sensor usage while maintaining measurement accuracy. The proposed method can be applied to other power electronic systems.